Countenance of the Indian Subcontinent and Iqbal Lahouri as a Theorist of Independence of Pakistan in the Poetry of Malik Alshoara Bahar - Jalayernia, Javad; Ahmadi, Abolghasem Amir; Sardehi, Ali Eshghi (Journal of History Culture and Art Research, 2017)
India and Iran have deep, ancient, ethnic, and cultural background in common in such a way that cultural, social, and political developments in the Indian land have always been observed by Iranian scholars and politicians. Persian language had been the official, courtier, and literature language of India since the fourth century AH until the beginning of British domination in India, approximately eight hundred years. During this period, many scientists and scholars have emerged in this country and valuable works had been created in Farsi. India has raised countless great politicians and scholars. Iqbal Lahouri is among them along with Gandhi, who was the leader of the peaceful protest movement against the British colonial. He raised the idea of establishing an Islamic state with the name of Pakistan after independence of India. An Iranian scholar Malik Alshoara Bahar, who lived in Iqbal’s time, frequently had cited Iqbal and developments in India. At the same time, Malik Alshoara Bahar was an active member of the Constitutional Movement Current during political developments in Iran. Therefore, naturally, Indian developments and ideas and thoughts of Iqbal Lahouri, as a Muslim theorist and scholar, had grown in his poetry.